An Empirical Study of Support for APB Opinion No. 16 - Brenner, Vincent C.; Shuey, Ronald E. (Journal of Accounting Research, 1972)
A mail questionnaire was sent to random samples of members of the Institute of Chartered Financial Analysts, the American Institute of Certified Public Accountants, and the American Accounting Association. The questionnaire asked the respondent to rank the three alternatives in their order of preference. The results of the study show that a majority of the respondents in each group preferred the Arthur Andersen & Co. proposal3